2016
DOI: 10.17219/acem/41048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thalidomide Combined with Interferon on Inhibiting Kasumi-1 Cell Proliferation

Abstract: with CR will relapse, with a long-term survival of less than 10%. In addition, treatment-related side effects are among the main factors limiting the clinical efficacy for AML treatment. It is of great practical significance to explore safe and effective new treatment options. Steins et al. [1] reported that the effective rate of thalidomide monotherapy in AML was 25% and that this treatment could improve transfusion dependence in patients.With improvements in treatment, the complete remission (CR) rate of you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, there are little or no effective benefits obtained from mono-therapies with thalidomide or its analogs in the treatment of solid tumors. Recently, thalidomide combined with typical chemotherapeutic drugs or immunomodulatory drugs showed curative effects in pre-clinical studies of tumor and leukemia [ 30 , 31 ]. Our presented study developed a combination of thalidomide with icotinib which showed distinctly synergic cytostatic and pro-apoptotic effects in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are little or no effective benefits obtained from mono-therapies with thalidomide or its analogs in the treatment of solid tumors. Recently, thalidomide combined with typical chemotherapeutic drugs or immunomodulatory drugs showed curative effects in pre-clinical studies of tumor and leukemia [ 30 , 31 ]. Our presented study developed a combination of thalidomide with icotinib which showed distinctly synergic cytostatic and pro-apoptotic effects in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide is rarely used alone in acute myeloid leukemia but when combined with IFN can inhibit Kasumi-1 cell proliferation, and is effective and tolerable in AML patients when combined with azacytidine. The three above-mentioned drugs alone have a limited effect on AML, so we attempted to use them in combination ( 20 , 21 ). In the previous study, 20 patients with hematological remission but AML1-ETO fusion gene positive AML were treated with routine dose of ITI regimen, 10 patients were negative after 1 month, and 4 patients decreased significantly after 2.8 months.…”
Section: Introductionmentioning
confidence: 99%